Corporate Governance - Recent Advances and Perspectives 2022
DOI: 10.5772/intechopen.101234
|View full text |Cite
|
Sign up to set email alerts
|

ESG for SMEs: Can the Proposal 2021/0104 for a European Directive Help in the Early Detection of a Crisis?

Abstract: With the proposal for a European Directive 2021/0104, the number of entities who will be required to prepare a non-financial statement (NFS) has been broadened. The directive provides that small and medium-sized enterprises (SMEs) may also voluntarily opt for drawing up a non-financial statement. It is therefore important to identify reporting standards containing key performance indicators (KPIs), tailored to the characteristics and structure of SMEs. In addition to the potential advantages in terms of improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Riva et al [107] concluded that the communication of non-financial information by SMEs has a dual objective. The disclosure demonstrated, firstly, the existence of a corporate governance structure and, secondly, represented a management and accounting tool had been designed to function adequately to ensure a firm operates as a going concern.…”
Section: Theoretical Implications For Future Researchmentioning
confidence: 99%
“…Riva et al [107] concluded that the communication of non-financial information by SMEs has a dual objective. The disclosure demonstrated, firstly, the existence of a corporate governance structure and, secondly, represented a management and accounting tool had been designed to function adequately to ensure a firm operates as a going concern.…”
Section: Theoretical Implications For Future Researchmentioning
confidence: 99%
“…However, at the same time, SMEs are also aware of their economic benefits while focusing on their green business [17], [18]. Thus, a critical triangulation of business survival during a turbulent economic condition, environmental protection, and, at the same time, a continuous innovation is a prime goal for any sector and any country [40]. On the one hand, green innovation invites risks, demands significant research and development (R&D) investment, and expert skill sharing for the SMEs.…”
Section: Editorialmentioning
confidence: 99%